Dramaturgy Of Advocates' Life In Forming Self Image - Wibowo, Adityo; Zakiah, Zakiah (LPPM Universitas PGRI Sumatera Barat, 2024)
The law is, for those who are able to show their prowess, they can be guaranteed to have a high standard fee, and vice versa. Impression management is not formed just like that, it must be managed well, especially the actors must be able to implement dramaturgical concepts. The aim of this research is to analyze the dramaturgy of an advocate's life in forming a self- image. Case Study Research Method directly to advocate Rasnoto., S.H., M.H as the key person in implementing the dramaturgical concept in forming self image. The front stage and back stage are carried out by maintaining appearance and character management so as to create impression management. Personal front includes verbal language and body language of the actor, then personal front and setting are further divided into appearance. Impression management is not formed just like that, it must be managed well, especially the actors must be able to implement dramaturgical concepts. The aim of this research is to analyze the dramaturgy of an advocate's life in forming a self-image. Case Study Research Method directly to advocate Rasnoto., S.H., M.H as the key person in implementing the dramaturgical concept in forming self image. The front stage and back stage are carried out by maintaining appearance and character management so as to create impression management. Personal front includes verbal language and body language of the actor, then personal front and setting are further divided into appearance and style (manner). The appearance shown by Rasnoto is an authoritative and firm appearance on the front stage and a style (manner) that is adapted to the trial situation and/or location of the case. The back stage is the place where Rasnoto shows the true image of himself. The real self of Rasnoto that he shows to his friends and family.